Expressed var gene repertoire and variant surface antigen diversity in a shrinking Plasmodium falciparum population - Carlos, Bianca C. [UNESP]; Fotoran, Wesley L.; Menezes, Maria J.; Cabral, Fernanda J.; Bastos, Marcele F.; Costa, Fabio T. M.; Sousa-Neto, Jayme A. [UNESP]; Ribolla, Paulo E. M. [UNESP]; Wunderlich, Gerhard; Ferreira, Marcelo U. (Elsevier B.V., 2016)
The var gene-encoded erythrocyte membrane protein-1 of Plasmodium falciparum (PfEMP-1) is the main variant surface antigen (VSA) expressed on infected erythrocytes. The rate at which antibody responses to VSA expressed by circulating parasites are acquired depends on the size of the local VSA repertoire and the frequency of exposure to new VSA. Because parasites from areas with declining malaria endemicity, such as the Amazon, typically express a restricted PfEMP-1 repertoire, we hypothesized that Amazonians would rapidly acquire antibodies to most locally circulating VSA. Consistent with our expectations, the analysis of 5878 sequence tags expressed by 10 local P. falciparum samples revealed little PfEMP-1 DBL1 alpha domain diversity. Among the most commonly expressed DBL1 alpha types, 45% were shared by two or more independent parasite lines. Nevertheless, Amazonians displayed major gaps in their repertoire of anti-VSA antibodies, although the breadth of anti-VSA antibody responses correlated positively with their cumulative exposure to malaria. We found little antibody cross-reactivity even when testing VSA from related parasites expressing the same dominant DBL1 alpha types. We conclude that variant-specific immunity to P. falciparum VSAs develops slowly despite the relatively restricted PfEMP-1 repertoire found in low-endemicity settings. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Plasmodium falciparum; Variant surface antigen; PfEMP-1; Antibodies; Amazon